PRE-ISLAMIC CULTURE AND RELIGION: - istadiyantha - - (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
Pre-Islamic Arab society is known as the people who inclined towards practicing racism, feudalism and patriarchy values. The pre-Islamic period was known to the Arabs as the period of living ignorant people. However, revolutionary momentum occurred after the emergence of Islam in the desert region. Radical Islam could change the Arab social order to the point where human values almost disappeared. That was thebeginning of learning society through educational values consistently with the Islamic teachings. This article provides sufficient evidence to examine how the educational knots began to disappear in the land ofHijaz. By examining the demographics of the culture of pre-Islamic Arab society, this article also attempts to take the segmentation of society as the basis for analyzing the emergence of Islamic teachings through theestablishment of the learning societies initiated by Prophet Muhammad (P.B.U.H).